Corporate Turnaround Strategy and the Resource-based View: A Matched Pair Study - Burks, William G (2011)
For decades corporate failure and the elusive turnaround has fascinated academics and captivated practitioners alike. Through drawing together the fields of business history, turnaround and that of strategic management, this study identifies that past research on turnaround has more often neglected the role of strategic change in the greater turnaround process; choosing to focus on operational change akin to retrenchment.